2020
DOI: 10.21203/rs.3.rs-53956/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MAP3K1 Expression is Associated With Progression and Poor Prognosis of Hormone Receptor-Positive, HER2-Negative Early-Stage Breast Cancer

Abstract: Background: MAP3K1 (Mitogen-Activated Protein Kinase Kinase Kinase 1) participates in the MAPK signal transduction pathway, responding to a number of mitogenic and metabolic stimuli, which may be related to breast cancer susceptibility and progression. In this study, we assessed whether overexpression of MAP3K1 promotes proliferation, migration, and invasion of breast cancer cells, and thus, affects the prognosis of hormone receptor (HR)-positive, human epidermal growth factor receptor 2 (HER2)-negative early-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…While α2 integrin expression correlates with poor overall survival and resistance to gemcitabine in high-stiffness matrices in pancreatic cancer 82 , poorly differentiated tumours were reported to express low levels of α2 integrin, while well-differentiated ones showed high levels of α2 integrin 83 . Consistent with our data showing a correlation between MAP3K1 levels and poor prognosis in PDAC patients, MAP3K1 expression correlates with progression and poor prognosis of hormone-receptor-positive, HER2-negative early-stage breast cancer patients 84 . Single-cell transcriptomes from matched primary tumours and metastasis from patient-derived xenograft models of breast cancer showed that metastasis displayed increased stress response signalling during metastatic progression 85 .…”
Section: Discussionsupporting
confidence: 93%
“…While α2 integrin expression correlates with poor overall survival and resistance to gemcitabine in high-stiffness matrices in pancreatic cancer 82 , poorly differentiated tumours were reported to express low levels of α2 integrin, while well-differentiated ones showed high levels of α2 integrin 83 . Consistent with our data showing a correlation between MAP3K1 levels and poor prognosis in PDAC patients, MAP3K1 expression correlates with progression and poor prognosis of hormone-receptor-positive, HER2-negative early-stage breast cancer patients 84 . Single-cell transcriptomes from matched primary tumours and metastasis from patient-derived xenograft models of breast cancer showed that metastasis displayed increased stress response signalling during metastatic progression 85 .…”
Section: Discussionsupporting
confidence: 93%
“…Sometimes, these CDKs and cyclins are upregulated or overexpressed leading to BC pathogenesis [ 68 ]. Upregulation of CDK2 and overexpression of cyclins E and B1 are observed in BC [ 69 , 70 ]. So, cell cycle arrest can be targeted for preventing BC progression.…”
Section: Anticancer Activity Of Polydatin On Liver Colon Bone Breast ...mentioning
confidence: 99%